The scaffoldings of aesthetics in journalism. On the thresholds of practice - Pérez Morales, Flor de Liz (2021)
The work presented here inquires into the notion of the aesthetic Arch that undermines the journalistic process. This arc refers to the construction of a theoretical-methodological spearhead that focuses the intention of aesthetics as a transversal resource in the journalistic process. The arch has three points of reference: The prosodic dimension of social discourse, The semiotics of the journalistic text and The poetics of journalistic discourse. The result is the product of an investigation and journalistic writing begun in 2008 in Tabasco-Mexico, whose main objective was oriented to analyze the role of aesthetics in journalistic practice, as a condition that houses, moves and draws the fibers of << feel >> on the route of the journalistic event. This aesthetic spectrum is reconfigured as a metamodel that houses the affectivities of a social-cultural journey.